The Concept of strategy and the Nueva Etnohistoria - Ramos, Alejandra; Chiappe, Carlos Maria (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2020)
In this article we review the use of the concept of strategy in the social sciences in particular in the field of Andean Ethnohistory. We focus on the phase called Nueva Etnohistoria (1980 and later), a moment of transcontinental consolidation of this interdisciplinary field. The sources of information used in this study consist of relevant collective publications and unpublished documents related to the organization of the I International Congress of Ethnohistory. With respect to these, we identify the meanings associated with the concept of strategy and reconstruct the debates that arise in its application, which are linked to current problems in the social sciences. Based on the foregoing, we propose the need to update the critical review of the concept of strategy.